Accounts Receivable Turnover Analysis and Company Merchandise Inventory Turnover - Sitti Hartati Haeruddin (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
This study aims to determine the level of trade receivables and merchandise inventory turnover at PT. Fajar Mas Karyatama. This research was conducted with quantitative descriptive techniques, namely by calculating the turnover of accounts receivable and merchandise inventory and collecting data by means of survey and documentation methods. The results showed that the turnover of trade receivables in 2011 was 15 times, in 2012 as many as 13 and 2013 as many as 12 or when calculated in the number of days for 2011 for 24 days, in 2012 for 28 days while in 2013 for 30 days. Meanwhile, merchandise inventory turnover in 2011 was 3 times, 2012 was 4 times and in 2013 4 times or when calculated in the average number of days the goods were stored in the warehouse in 2011 for 120 days, in 2012 for 90 days and for 2013 for 90 days.